Mesoporous bamboo charcoal-gold nanoparticles as a support for efficient enzyme immobilization - Guihong Yao; Yun Ling; Tong Liu; Shige Xing; Meiyi Yao; Wei Guo; Feng Zhang (Journal of Future Foods)
Herein, a green and facile enzyme immobilization method was developed by immobilizing enzymes on the bamboo charcoal (BC) through gold-mediated adsorption under mild conditions (no organic solvents were required). Lipase PS was used as the model enzyme, and the obtained immobilized lipase (PS@BC-Au) exhibited a high immobilization efficiency (93.9%) and enzyme loading capacity (234.78 µg/mg). The half-life of PS@BC-Au was found to be 362.8 min, which is approximately 1.3 and 2 times longer than that of the free enzyme (185.3 min) and the immobilized enzyme without gold (PS@BC, 275.0 min). Furthermore, PS@BC-Au and PS@BC exhibited up to 63.9% and 47.1% of residual activity after 10 cycles, respectively. Interestingly, the gold nanoparticles in the immobilized system can improve the catalytic efficiency. Consequently, BC, with its porous structure, good stability, large surface area, low cost, and environmental-friendly properties, can serve as a promising support for enzyme immobilized application.